2010
DOI: 10.1111/j.1558-5646.2010.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Modularity and Scaling in Fast Movements: Power Amplification in Mantis Shrimp

Abstract: Extremely fast animal actions are accomplished with mechanisms that reduce the duration of movement. This process is known as power amplification. Although many studies have examined the morphology and performance of power-amplified systems, little is known about their development and evolution. Here, we examine scaling and modularity in the powerful predatory appendages of a mantis shrimp, Gonodactylaceus falcatus (Crustacea, Stomatopoda). We propose that power-amplified systems can be divided into three unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 115 publications
(219 reference statements)
8
100
1
Order By: Relevance
“…For many taxa, the outcome of animal contests is influenced by body size 447 (Haley, Deutsch, & Le Boeuf, 1994;Wells, 1988) because this attribute is generally 448 correlated with strength and the ability to inflict injury (Archer, 1988;Parker, 1974). For 449 example, in mantis shrimp, Gonodactylaceus falcatus, larger individuals have a physical 450 advantage over smaller individuals because both spring and strike force of the raptorial attack 451 are correlated positively with body size (Claverie, Chan, & Patek, 2011). 452…”
Section: Discussion 423mentioning
confidence: 99%
“…For many taxa, the outcome of animal contests is influenced by body size 447 (Haley, Deutsch, & Le Boeuf, 1994;Wells, 1988) because this attribute is generally 448 correlated with strength and the ability to inflict injury (Archer, 1988;Parker, 1974). For 449 example, in mantis shrimp, Gonodactylaceus falcatus, larger individuals have a physical 450 advantage over smaller individuals because both spring and strike force of the raptorial attack 451 are correlated positively with body size (Claverie, Chan, & Patek, 2011). 452…”
Section: Discussion 423mentioning
confidence: 99%
“…Previous work by Claverie & Patek [31] examined rates of morphological disparity across mantis shrimp raptorial segments using composite, geometric morphometrics measurements that reflected the interdependence (modularity) of changes in size and shape across the segments (e.g. [60,61]). They found that disparity accumulated more quickly in spearers than in smashers.…”
Section: Discussionmentioning
confidence: 99%
“…An intraspecific analysis found that the functional subdivision into engine, amplifier and tool also corresponds to the pattern of developmental integration, where those three elements form separate modules [55]. A comparative analysis across the clade showed that the tool behaves as an evolutionary module separate from engine and amplifier [26].…”
Section: (C) Functional Integrationmentioning
confidence: 99%
“…An excellent example of a study that links functional considerations to developmental and evolutionary integration is the analysis of variation in the predatory appendages of mantis shrimp [26,55]. An intraspecific analysis found that the functional subdivision into engine, amplifier and tool also corresponds to the pattern of developmental integration, where those three elements form separate modules [55].…”
Section: (C) Functional Integrationmentioning
confidence: 99%
See 1 more Smart Citation